LOCAL GOVERNMENT IN PORTUGAL AND IN THE WORLD – A COMPARATIVE LAW: COMPARISON BETWEEN THE PORTUGUESE, EUROPEAN AND NORTH AMERICAN REGIMES (Isagoge - Journal of Humanities and Social Sciences, 2025)
Local power has acquired a growing importance in the government and administration of countries. With all the decentralization that has been promoted in recent years, it will be very interesting to promote an analysis of how the democratic systems have been organized, both in our country and in the rest of Europe, and then make a bridge to the North American system, which is so special. This article will be important for any reader to understand how local systems are arranged, both in Europe and in the United States, and thus better understand it. Thus, after doing a literature review and studying the various models, it has been possible to draw conclusions and make a critique of both models, which have their advantages and disadvantages in terms of organization and form of action.
Keywords: Local Government; Municipalities; Portugal; Europe; United States of America